2014
DOI: 10.1063/1.4891443
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectricity and ferroelectricity in biomaterials: Molecular modeling and piezoresponse force microscopy measurements

Abstract: Piezoelectricity is one of the important functional properties inherent to many biomaterials. It stems from the non-centrosymmetric crystal structure of most biopolymers including proteins, polysaccharides, and lipids. Understanding the relationship between the generated electric field and applied mechanical stress has become the main motivation to studying piezoelectricity in biological systems and artificial biomaterials at the nanoscale. In this work, we present a review of the piezoelectric and ferroelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 85 publications
0
46
0
5
Order By: Relevance
“…Поэтому после проведенного нами ранее (в аналогичных наших работах [12,16,17]) тестирования и сравнения результатов с методами ТФП, мы используем далее в данной работе РМ3 метод для сравнительно больших ПВДФ и П(ВДФ-ТрФЭ) систем и для более длинных (протяженных во времени и требующих больше оперативной пямяти) молекулярно-динамических расчетов. Более подробно молекулярные модели описаны в работах [12,16,17,19,32], и дополнительно детали представлены в недавно опубликованной работе [33]. Проведенные нами серии предварительных расчетов показали, что для оптимизации и МД прогонов в таких цепочках результаты расчетов в неограниченном ХФ (НХФ) и ограниченном ХФ (ОХФ) приближениях практически совпадают в пределах заданной точности.…”
Section: применяемые методы и вычислительные деталиunclassified
See 2 more Smart Citations
“…Поэтому после проведенного нами ранее (в аналогичных наших работах [12,16,17]) тестирования и сравнения результатов с методами ТФП, мы используем далее в данной работе РМ3 метод для сравнительно больших ПВДФ и П(ВДФ-ТрФЭ) систем и для более длинных (протяженных во времени и требующих больше оперативной пямяти) молекулярно-динамических расчетов. Более подробно молекулярные модели описаны в работах [12,16,17,19,32], и дополнительно детали представлены в недавно опубликованной работе [33]. Проведенные нами серии предварительных расчетов показали, что для оптимизации и МД прогонов в таких цепочках результаты расчетов в неограниченном ХФ (НХФ) и ограниченном ХФ (ОХФ) приближениях практически совпадают в пределах заданной точности.…”
Section: применяемые методы и вычислительные деталиunclassified
“…Основываясь на наших предыдущих PM3 исследованиях [12,16,17,19,32,33], показавших их хорошую достоверность при сравнении с другими методами расчетов и экспериментом, мы предполагаем, что применение моделей с шестью мономерами и десятью мономерами будет достаточно для исследования переключения поляризации в первом приближении в таких нанопленках.…”
Section: применяемые методы и вычислительные деталиunclassified
See 1 more Smart Citation
“…Apparently, new materials classes based on natural tissue components, such as amino acids, peptides, or lipids, should be explored in view of their natural biocompatibility and variability. 8 Recent studies on the simplest amino acid glycine have demonstrated that it is a suitable material with apparent ferroelectric properties and square piezoresponse hysteresis loops at room temperature. 9 The advantage of glycine is not only its simplicity and ability to serve as a building block for proteins but also its polymorphic nature allowing simple yet effective means to form piezoelectric composites comprising several phases of the same material (e.g., ferroelectric-dielectric or ferroelectric-piezoelectric).…”
mentioning
confidence: 99%
“…Finally, it is also worth noting, that the value of the polarization and the surface charge density (P ~ 0.0038 C/m 2 ) obtained in view of the general law of the electromechanical coupling (that is the connection between polarization and piezoelectric coefficients, inherent of all ferroelectrics) [63,64] leads to the value of the piezoelectric coefficient of the order of d ~ 15.7 pm/V, which only twice larger than values ~ 7.62-8.48 pC/N (or pm/V) measured by Halperin et al on tibia bone samples by piezoresponse force miscroscopy [64,65]. As we discussed above (section 2.2) such deviation could occur by averaging the registered piezoelectric signal from different grains with various local polar states, fluctuated in crosssection of the native tibia bones samples.…”
Section: Main Principles and Features Of Hap Surfaces Charges And Elmentioning
confidence: 99%